2020
DOI: 10.1111/een.12966
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional plant‐mediated interactions between rhizobacteria and shoot‐feeding herbivorous insects: a community ecology perspective

Abstract: 1. Plants interact with various organisms, aboveground as well as belowground. Such interactions result in changes in plant traits with consequences for members of the plant-associated community at different trophic levels. Research thus far focussed on interactions of plants with individual species. However, studying such interactions in a community context is needed to gain a better understanding.2. Members of the aboveground insect community induce defences that systemically influence plant interactions wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 110 publications
0
35
0
Order By: Relevance
“…For example, early nodule formation in legumes can be inhibited by pathogens (López et al, 2017;Rao et al, 1987), although herbivory can promote abundance and greater size of nodules (Heath & Lau, 2011;Simonsen & Stinchcombe, 2014). Recent syntheses suggest while herbivores and pathogens alter benefits of microbes for plants, the plant-mediated mechanisms underlying these interactions need further investigation (Friman et al, 2020;Pangesti et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For example, early nodule formation in legumes can be inhibited by pathogens (López et al, 2017;Rao et al, 1987), although herbivory can promote abundance and greater size of nodules (Heath & Lau, 2011;Simonsen & Stinchcombe, 2014). Recent syntheses suggest while herbivores and pathogens alter benefits of microbes for plants, the plant-mediated mechanisms underlying these interactions need further investigation (Friman et al, 2020;Pangesti et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Beneficial below-ground microorganisms may influence the performance of herbivores via two major functional pathways, that is, enhancement of nutrition promoting plant growth and development, which in turn may favor the herbivores, or induced systemic resistance (ISR), which may disfavor the herbivores, or the combination thereof ( Kempel et al, 2009 ; Pineda et al, 2010 ; Gamalero and Glick, 2011 ; Friman et al, 2021b ). Many studies of above-belowground interactions showed that beneficial soil microorganisms such as free-living rhizobacteria can induce systemic resistance in above-ground plant parts and enhance the level of protection against herbivorous attackers ( Zehnder et al, 1997 ; Koricheva et al, 2009 ; Khoshfarman-Borji et al, 2020 ; Ruiu, 2020 ; Friman et al, 2021a ).…”
Section: Discussionmentioning
confidence: 99%
“…In terrestrial ecosystems, plants are the link between below- and above-ground communities, which may in consequence either indirectly, by altering plant traits, or directly, by moving up or down in the plant, interact with each other. During the last two decades, research on below-aboveground interactions has immensely intensified and many studies have focused on effects that cascade up and down between the communities of both subsystems ( Van der Putten et al, 2001 ; Pineda et al, 2010 ; Hoffmann et al, 2011a , b ; Friman et al, 2021b ). Plant-mediated below-aboveground interactions involving micro-organisms of the rhizosphere may occur between plant-associated and/or free-living microorganisms ( Bezemer and van Dam, 2005 ; Coskun et al, 2017 ; Dellagi et al, 2020 ), between micro-organisms and herbivores ( Hoffmann et al, 2009 ; Patiño-Ruiz and Schausberger, 2014 ; Disi et al, 2019 ; Friman et al, 2021a ) and, in turn, between micro-organisms and the herbivores’ natural enemies ( Hoffmann et al, 2011a , b ; Pineda et al, 2013 ; Gadhave et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported effects of herbivory on mycorrhizal colonization, ranging from an increase to no effect to a decrease [88,89]. To date, these findings have not yet been tested in the context of ISR, even though they could potentially open up new insights into top-down effects on ISR when using a community approach [90]. Not much is known about the effects of natural enemies of insect herbivores on ISR.…”
Section: Impact Of Biotic Factors On the Activation And Effectiveness Of Isrmentioning
confidence: 99%